2017
DOI: 10.1007/s11701-017-0741-x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted vs. laparoscopic donor nephrectomy: a retrospective comparison of perioperative course and postoperative outcome after 1 year

Abstract: Safety is of utmost importance in live donor nephrectomies. In this study, we describe our initial experience with robot-assisted laparoscopic donor nephrectomy (RDN) in comparison with the standard laparoscopic donor nephrectomy (LDN). We retrospectively reviewed 95 patients who either underwent RDN or LDN performed by a single surgeon from 2011 to 2016 at a tertiary institution. Donor perioperative course and postoperative outcome along with recipient outcomes were compared. Of the 95 cases, 73 were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 30 publications
4
33
1
1
Order By: Relevance
“…Mean OT and mean CT ranged from 139 to 306 minutes and from 82 to 120 minutes, respectively. Three comparative studies found mean OT to be significantly longer in RALDN series with respect to LDN [4, 13, 16]. Mean OT of RALDN was also significantly longer than open donor nephrectomy (ODN) and hand-assisted retroperitoneoscopic donor nephrectomy (HARP) [4, 7, 13].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mean OT and mean CT ranged from 139 to 306 minutes and from 82 to 120 minutes, respectively. Three comparative studies found mean OT to be significantly longer in RALDN series with respect to LDN [4, 13, 16]. Mean OT of RALDN was also significantly longer than open donor nephrectomy (ODN) and hand-assisted retroperitoneoscopic donor nephrectomy (HARP) [4, 7, 13].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Janki et al found mean OT of RALDN procedures 1-19 to be significantly longer than RALDN procedures 40-59 (median OT of 240 and 172.5 minutes, respectively) [13]. In the study by Yang et al, the OT of RALDN approached that of LDN with each subsequent procedure over the course of the robotic cases and the standard OT of LDN was reached at the 22nd case [16].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations